PENGARUH BEBAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MODERASI ( Studi Pada Sekretariat Daerah Kabupaten Rembang ) - Moh. Nur Said, 1352020026 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to analyze the effects of workload and competence to employee performance with organizational commitment as a moderation in the Regional Secretariat of Rembang Region. The population in this study was a civil servant at the Regional Secretariat of Rembang Region, amounting to 168 people. Sampling by using the "census method" Data obtained by questionnaire to 168 employees.The result of this studi correctly proved that modelâs ability to explain the effect of variable workload, competence is equal to 9.1% of the employees performance. While others at 80.9% is explained by variables outside the model. The results of hypothesis, the effects of workload is negative and significant to employee performance, competency positive and significant to the performance of employees, organizational commitment proved to be a moderation (strengthen) the effect of workload on employee performance and organizational commitment is not proved to be a moderating effect of competence on employee performance.. Keywords : workload, competency, organizational commitmentÂ  and employee performance